Analysis of the Evaluation of the Affective Domain of Islamic Education in the Merdeka Curriculum - Fatwa Azmi Syahriza; Imroatul Chasanah; Sinta Dewi Kumala; Mohammad Asrori (Universitas Muhammadiyah Enrekang, 2023)
Learning evaluation is the process of systematically collecting, analysing and interpreting information to determine the achievement of learning objectives. One of the important components in learning evaluation is the affective/attitude domain. The purpose of this research is to find out: (1) understanding the learning evaluation of the affective domain of the PAI subject; (2) indicators of the evaluation of the affective domain of the PAI subject in the Merdeka Curriculum; (3) planning and implementation of the evaluation of the affective domain of the PAI subject in the Merdeka Curriculum. This study uses a qualitative approach by describing and elaborating on the design of the affective domain evaluation instrument for the PAI subject in implementing the Merdeka Curriculum. The data collection technique used in this research is literature study. The primary data source used is the Merdeka Belajar curriculum policy published by the Ministry of Education and Culture of the Republic of Indonesia. The secondary data sources are obtained through national and international journal articles and other book sources that can help researchers related to the design of affective domain evaluation instruments for Islamic education in the Merdeka Curriculum. The results of this study indicate that affective is a domain related to mentality and values, in the form of feelings, interests, attitudes, emotions or values. In the learning of the Merdeka Curriculum, there are no terms for cognitive, affective, and psychomotor assessments, but the Merdeka Curriculum is known as formative and summative assessments. Affective evaluation techniques can be carried out through observation, self-assessment, peer-review and journals.